2013
DOI: 10.2166/wh.2013.130
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Escherichia coli and Enterococcus spp. to selected antimicrobial agents present in municipal wastewater

Abstract: In this study, the susceptibility to erythromycin (E) and to trimethoprim/sulfamethoxazole (SXT) among isolates of Enterococcus spp. and Escherichia coli was tested, respectively. Both fecal indicators were detected and isolated from raw (RW) and treated wastewater (TW) as well as from samples of activated sludge (AS) collected in a local wastewater treatment plant (WWTP). Biodiversity of bacterial community in AS was also monitored using polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 1 publication
2
21
0
Order By: Relevance
“…The Shannon biodiversity index was calculated. It expresses the diversity of microbial genotypes in an investigated environment, which in this study was the surface of the document (32).…”
Section: Methodsmentioning
confidence: 99%
“…The Shannon biodiversity index was calculated. It expresses the diversity of microbial genotypes in an investigated environment, which in this study was the surface of the document (32).…”
Section: Methodsmentioning
confidence: 99%
“…Many of the studies report an inventory of antibiotic resistance genes (Nesme et al 2014) and many address bacteria in aquatic environments (for review see Kümmerer 2009b) or soils (Gatica and Cytryn 2013). The resistance of bacterial species used as fecal indicators was also often investigated (Luczkiewicz et al 2013;Servais and Passerat 2009). However, despite the proliferation of environmental antibiotic studies in general, relatively few have considered the impact of antibiotics on Becosystem health^ (Gu 2014).…”
Section: Antibiotics In the Environmentmentioning
confidence: 99%
“…To date, besides sul 1, only two other genes encoding sulfonamide resistance ( sul 2–3) have been identified (Sköld 2001 ) . The sul 2 gene was considered to be mainly located on small non-conjugative plasmids (Radstrom et al 1991), whereas s ul 3 was reported in animals as well as human-liked sources (Luczkiewicz et al 2013; Perreten and Boerlin 2003) and associated with non-classic class 1 integrons (Antunes et al 2005). Most previously described class 2 integrons contain the same array of four gene cassettes, three antibiotic resistance gene cassettes ( dfrA1 , sat , and aadA1 ), conferring resistance to trimethoprim, streptothricin, and spectinomycin/streptomycin, respectively, and the orfX cassette of unknown function (Flores et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Since SMX is excreted mainly in unchanged form, it has been also frequently found in the sewage systems. In the effluents from wastewater treatment plants (WWTPs), SMX was detected in the range from 0.004 to 9.46 μg/L (Trovó et al 2009; Loos et al 2010; Fatta-Kassinos et al 2011; Luczkiewicz et al 2013), while in the receiving waters up to 4 μg/L (Barnes et al 2008). …”
Section: Introductionmentioning
confidence: 99%